Effect of Hypertension on the Left Atrium Using Tissue Doppler Imaging Echocardiography - Mohammed, Dhuha Qasim; Al-Aboodi, Asaad Hasan Noaman (Medical Science Journal for Advance Research, 2024)
Background: left atrial enlargement plays a crucial role in increasing the risk of cardiovascular events. this is most of the time proceeded by left ventricular hypertrophy (LVH) which is caused by the effect of hypertension. Aim: evaluate LA function using tissue Doppler imaging of two-dimensional volumetric parameters in subjects with essential hypertension to establish the prognostic elements of arterial hypertension. Patient and Methods: cross-sectional analytic study. The study samples were obtained from the Al-Furat Teaching Hospital’s Echocardiographic Consultation Unit in the Al-Najaf Governorate between 1st September 2023, and 20th April 2024. Sixty-eight known cases of hypertensive patients with age of (18-60 years old). All patients are males and females. Clinical evaluation, anthropometric assessments, Doppler echocardiography as well as TDI study were done for each one of them to assess the left atrial volumes and function. Results: the hypertensive patients show a significant difference in accordance with weight, height, age, and BSA (all P<0.05). At the same time, there was a significant difference in S and E wave parameters between patients with normal and abnormal LVM. However, all these parameters are abnormal in all patients with and without LVH. These parameters are abnormal according to the normal reference range. Conclusion: TDI with color-coded Q-analysis can detect the early LA wall abnormality caused by hypertension even before the obvious structural changes appear in LV and LA.